CHARACTERISTICS OF FISH COLLECTING VESSELS FLEET BASED IN NIZAM ZACHMAN JAKARTA OCEAN FISHING PORT (PPS) - Muthiara; Apriliani, Izza Mahdiana; Suryana, Asep Agus Handaka; Putra, Pringgo Kusuma Dwi Noor Yadi (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Nizam Zachman Jakarta Ocean Fishing Port (PPS) generally produces catches for export activities, so it requires transportation that helps the efficiency of catch distribution. It should be noted that the mode of transportation in the form of fish collecting vessels that help the efficiency of catch distribution still needs to be expanded to comprehensive studies. This study aims to identify the characteristics of fish-collecting vessels based on size and general arrangement, analyze the licensing system applied, and analyze the work scheme of fish-collecting vessels based in PPS Nizam Zachman Jakarta. The method used in this research is descriptive method with data collecting techniques through observation, interviews, and literature studies. The results showed that the size of fish collecting vessels based in PPS Nizam Zachman Jakarta is in the range >100GT->300GT, with the layout on the ship mainly used for refrigerated holds and cold storage. The types of fish-collecting vessels consist of sea-to-port and port-to-port fish collecting vessels. The licensing system for fish transport vessels consists of registration to become a fishing vessel and sailing licenses. The work scheme of fish collecting vessels consists of preparation for operations, fish transportation operations, and handling fish catches at the port. Key words: fish transportation, licensing system, operational scheme, port to port, sea to port